Reverse-engineering the FLT3-PI3K/AKT axis to enhance TILs function and improve prognosis in ovarian and cervical cancers - Feng Hao; Zhang Yan; Luo Shen; Wang Hui; Qiu Ling; Yang Xiaoyu; Jiang Hua (Journal of Ovarian Research)
Abstract Background Ovarian cancers (OC) and cervical cancers (CC) have poor survival rates. Tumor-infiltrating lymphocytes (TILs) play a pivotal role in prognosis, but shared immune mechanisms remain elusive. Methods We integrated single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics (ST) to explore immune regulation in OC and CC, focusing on the PI3K/AKT pathway and FLT3 as key modulators. Seurat and Harmony were employed for batch correction and dimensionality reduction. FLT3 expression was mapped with spatial data from 10 × Genomics. Results FLT3, identified as a regulator through the PI3K/AKT pathway, showed positive correlations with T cells, NK cells, and B cells. FLT3-high regions exhibited increased immune infiltration, particularly in CC, enhancing survival outcomes. Conclusion This study provides the first spatially resolved evidence of FLT3's immune-modulatory role in OC and CC, positioning it as a promising immunotherapeutic target. FLT3-targeted strategies may offer new options for patients resistant to conventional therapies.